2021
DOI: 10.1021/acs.estlett.1c00553
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic Labeling Reveals Microbial Methane Oxidation Coupled to Fe(III) Mineral Reduction in Sediments from an As-Contaminated Aquifer

Abstract: Although arsenic (As) groundwater contamination in South and Southeast Asia is a threat to human health, mechanisms of its release from sediment to groundwater are still not fully understood. In many aquifers, Fe­(III) minerals are often the main hosting phases for As and their stability is crucial for As mobility. Recently, a new mechanism for As mobilization into groundwater was proposed with methane (CH4) serving as an electron donor for microbially mediated reductive dissolution of As-bearing Fe­(III) mine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 38 publications
0
7
2
Order By: Relevance
“…Although our previous study showed anaerobic CH 4 oxidation coupled with Fe(III) reduction in this aquifer (Glodowska, 2020; Pienkowska et al, 2021), the CH 4 concentration in uninoculated microcosms in this experiment remained stable until the end of incubation (65 days). This discrepancy is likely due to the much shorter incubation period of this experiment compared to our previous study, where Fe-DAMO activity was observed only after 100 days of incubation.…”
Section: Resultscontrasting
confidence: 62%
“…Although our previous study showed anaerobic CH 4 oxidation coupled with Fe(III) reduction in this aquifer (Glodowska, 2020; Pienkowska et al, 2021), the CH 4 concentration in uninoculated microcosms in this experiment remained stable until the end of incubation (65 days). This discrepancy is likely due to the much shorter incubation period of this experiment compared to our previous study, where Fe-DAMO activity was observed only after 100 days of incubation.…”
Section: Resultscontrasting
confidence: 62%
“…92 Moreover, genes related to methane oxidation did not have observable Spearman correlations with those associated with Fe(III) reduction genes, although methane oxidation coupled As-bearing Fe(III) reduction was reported as one of the key As-mobilizing pathways in other high-As groundwaters. 17,18,93 Collectively, our data suggest that methane oxidation may have limited contributions to Fe(III) reduction in the study area.…”
Section: ■ Materials and Methodsmentioning
confidence: 69%
“…Only low abundances of genes related to methane oxidation ( mmoXYBC , average FPKM from 0.11 to 1.23) and undetectable genes underpinning methanogenic processes ( mcrABC ) were found in our datasets, potentially due to the significant downregulation of the key enzymes regulating methanogenesis by ammonium . Moreover, genes related to methane oxidation did not have observable Spearman correlations with those associated with Fe­(III) reduction genes, although methane oxidation coupled As-bearing Fe­(III) reduction was reported as one of the key As-mobilizing pathways in other high-As groundwaters. ,, Collectively, our data suggest that methane oxidation may have limited contributions to Fe­(III) reduction in the study area.…”
Section: Resultsmentioning
confidence: 99%
“…59 We found one OTU (OTU00368) that was classified within the Methanoperedenaceae family, which is known to contain a species implicated in anaerobic iron- and manganese-mediated methane oxidation. 58,63–66 OTU00368 peaked in relative abundance (0.1%) at 0 cm depth, then decreased to 0.04% at 0.25 cm, which is within the surficial, flocculant layer of Fe( iii )-oxides and corresponds to the layer where highly reactive Fe( iii )-oxides were detected. Within the top 0.5 cm, the Methanoperedenaceae would get relatively fresh and thermodynamically-favorable Fe( iii )-oxides from authigenic production by abundant FeOB and methane diffusing upwards from depth.…”
Section: Resultsmentioning
confidence: 94%